Penguatan Pemahaman Ekonomi dan Keuangan Syariah di Pondok Pesantren Al Ihsan Boarding School - A, Adriani (Yayasan Daarul Huda Kruengmane, 2025)
This community service activity was implemented by lecturer at the Faculty of Islamic Economics and Business Lukman Edi Pekanbaru. This activity aims to introduce the Shariah-based economic and financial system, as well as about riba and its future impact to students. The target of this activity is the students of class XII which consists of classes with majors in social studies and science. The conclusion of the results of these MPH activities, namely the minimum economic and financial literacy of students, then through this socialization can positively impact students by opening up insights and knowledge on the opportunities of understanding Shariah economics and finance, and the hope is that online students and students beware of gambling applications. dealing with economics and finance.